Adaptive citizenship as a response to the era of globalization and digitalization - M. Asif Nur Fauzi; Toto Suryadi; Mohammad Firman; Sukron Mazid (C-DISC, 2026)
The era of globalization and digitalization has transformed citizenship into a dynamic construct that requires individuals to continuously adapt to rapid social and technological changes. This study examines the concept of adaptive citizenship as a response to the challenges emerging from globalization and the digital age. Employing a qualitative literature review, the study analyzes national and international peer-reviewed journal articles published between 2019 and 2024, supplemented by relevant academic books and policy documents. The data were analyzed using qualitative content analysis, including data reduction, categorization, interpretation, and conclusion drawing, to identify key themes, patterns, and conceptual frameworks associated with adaptive citizenship. The findings identify four core dimensions of adaptive citizenship: digital literacy, global awareness, social participation, and national identity. Together, these dimensions provide a comprehensive framework for developing citizens who are critical, ethically responsible, and firmly rooted in national values while remaining responsive to global transformations. The study underscores the importance of reorienting citizenship education toward a more contextual, competency-based, and adaptive approach that prepares learners to navigate the complexities of an increasingly interconnected and digitalized world.